2011
DOI: 10.1160/th10-09-0572
|View full text |Cite
|
Sign up to set email alerts
|

Functional mapping of factor VIII C2 domain

Abstract: The factor VIII (FVIII) is a cofactor of the coagulation cascade. The FVIII C2 domain is a critical domain that participates in the interactions with the von Willebrand factor and the phospholipidic surfaces. To assess the importance of each residue of this domain in the maintenance of the structure and the function of FVIII, a number (n=139) of mutants were generated by substituting the original residues, from Ser2173 to Gly2325, by an alanine. Mutants were built within a complete B domain-deleted FVIII and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…We used an in vitro mutagenesis screening where almost all of the residues of the A2 and the C2 domains were mutated to alanine 30 , 31 . The A2 domain is important for the FVIII activity because in addition to its role in stabilizing the protein structure 32 , it contains a binding site for FIXa (ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used an in vitro mutagenesis screening where almost all of the residues of the A2 and the C2 domains were mutated to alanine 30 , 31 . The A2 domain is important for the FVIII activity because in addition to its role in stabilizing the protein structure 32 , it contains a binding site for FIXa (ref.…”
Section: Resultsmentioning
confidence: 99%
“…The ELISA assay was used to assess the efficiency of FVIII mutant constructs expression and secretion (often referred as antigen assay because they measure both functional and nonfunctional FVIII proteins by the amount of FVIII antigen (protein) immobilized on the ELISA plate. Two commercial kits were used to apply the “sandwich” method, where the antigen (FVIII construct) is captured between two layers of antibodies 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…This could suggest that the major components necessary for sufficient membrane interaction for FVIIIa in vivo are non-specific contributions, such as hydrophobic partitioning and electrostatics, consistent with the results of the simulations described here. Furthermore, alanine-scanning the FVIII C2 domain within a complete B-domainless FVIII molecule has suggested that primarily resides in structural regions of the domain (β-sheet forming residues) are functionally sensitive to mutation 63 . In addition to these general observations, our results further implicate R2163 in FVIII C1, and R2220 and R2320 in FVIII C2 as potentially critical residues in that they are the only basic residues capable of forming direct interactions with PS lipids.…”
Section: Resultsmentioning
confidence: 99%
“…1). Preliminary in silico mutagenesis was performed at this position with every other 19 amino acids (AA) using in-house software 21 . It was found that most AA replacements were deleterious.…”
Section: Resultsmentioning
confidence: 99%
“…The mutational energy cost for replacing Glu112 residue was performed by computing ΔΔE E→K = ΔE K - ΔE E , 46 where ΔE K and ΔE E are the relative potential energies of the mutant Lys and WT Glu in an optimized protein environment of the crystal structure, respectively 21 . The potential energy is the sum of vdw and Coulombic interactions.…”
Section: Methodsmentioning
confidence: 99%